Antibacterial potential of leaf and fruit of citrus extract (Citrus aurantifolia) against klebsiella oxytoca - Zuraidah Zuraidah; Widiasari Widiasari; Wati Oviana (STKIP Persada Khatulistiwa Sintang, 2023)
Antimicrobial agents play a crucial role in decreasing the impact of infectious diseases worldwide. Many medicinal plants have been identified as rich sources of natural antimicrobial compounds that can be used as an alternative to traditional treatments for bacterial infections. Indonesia, particularly in the Aceh region, has a warm and humid climate that supports a diverse range of plants that have medicinal properties. One example is the lime (Citrus aurantifolia) which can be used for medicinal purposes.This study aimed to determine the inhibitory effects of leaves and fruit extracts of lime on the growth of Klebsiella oxytoca.The method used was an experimental method with a post-test only control group design. The results showed that both types of extracts contain flavonoid, alkaloid, and saponin compounds. However, triterpenoids were only found in the fruit extract, and steroids were only found in the leaf extract. The antimicrobial test of lime fruit and leaf extracts against Klebsiellaoxytoca bacteria showed that both types of extracts were able to inhibit the growth of the test bacteria at all concentrations.